With Child in Mind Studies of the Personal Encounter with Infertility - Sandelowski, Margarete (Studies in Health, Illness, and Caregiving, 2016)
Sandelowski retells the stories of couples who want to have children, but cannot. In their own words, the couples candidly discuss what it means to be infertile and how infertility ultimately affects their views of themselves, their values, their children, and their interactions with others. Information from more than 500 intensive interviews with women and couples forms the core of With Child in Mind